Associations Between Leisure-Time Physical Activity Level and Peripheral Immune Cell Populations in the US General Population, Analysis of the National Health and Nutrition Examination Survey Data, 1999-2018 - Dan Lin; Cheryl L. Thompson; Djibril M. Ba; Joshua E. Muscat; Shouhao Zhou; Connie J. Rogers; Kathleen M. Sturgeon (SpringerOpen, 2023)
Abstract Background Chronic levels of inflammation are associated with higher risk of many chronic diseases. Physical activity (PA) lowers the risk of cancer, cardiovascular disease (CVD), diabetes and others. One mechanism for PA-induced protection may be through the immune system. We investigated the association between leisure-time PA and peripheral immune cell populations in a large nationally representative sample of the US general population. Methods A total of 17,093 participants [mean (SE) age of 41.6 (0.3) years] of the National Health and Nutrition Examination Survey 1999-2018 were included. Self-reported leisure-time PA was converted to metabolic equivalent of task hours per week (MET-hrs/wk). White blood cell (WBC) count, WBC ratios, and platelet count were derived. Multivariable linear regression analyses were used to estimate associations between leisure-time PA level and peripheral immune cell populations. Multivariable logistic regression analyses were used to estimate associations between leisure-time PA and metrics of WBC count and neutrophil-to-lymphocyte ratio (NLR) which may predict mortality. Results A higher leisure-time PA level was associated with a lower WBC count (> 14.0 vs. < 1.2 MET-hrs/wk adjusted mean (95% confidence interval [CI]): 7.12 (6.86, 7.38) vs. 7.38 (7.12, 7.64) 1000 cells/μL, P trend < 0.001) and a lower NLR (> 14.0 vs. < 1.2 MET-hrs/wk adjusted mean (95% CI) 2.04 (1.90, 2.18) vs. 2.13 (1.99, 2.28), P trend = 0.007). Leisure-time PA level was not associated with lymphocyte-to-monocyte ratio (LMR; P trend = 0.25) or platelet-to-lymphocyte ratio (PLR; P trend = 0.69). Compared to the lowest leisure-time PA level (< 1.2 MET-hrs/wk), the highest leisure-time PA level (≥ 14.0 MET-hrs/wk) was associated with a lower probability of a high WBC count (> 8.1 × 109 cells/L; odds ratio [OR] = 0.76, 95% CI = 0.66-0.88) and high NLR (> 2.68; OR = 0.84, 95% CI = 0.72-0.99), which may predict CVD and all-cause mortality. The highest leisure-time PA level also linked to a lower probability of a high WBC count (≥ 8.3 × 109 cells/L; OR = 0.76, 95% CI = 0.66-0.88), which may predict cancer mortality. Conclusions We observed an inverse association between leisure-time PA level, WBC count, and NLR, particularly for neutrophil levels. These results suggest that participants at higher levels of leisure-time PA may have lower levels of inflammation, which may be important for future chronic disease outcomes.